Peningkatan Hasil Belajar PPKn Menggunakan Model Problem Based Learning dalam Nuansa Kurikulum Merdeka di Sekolah Dasar - Aisyah Anggraeni; Muhammadi Muhammadi (Universitas Negeri Padang, 2023)
This study aims to describe how to improve learning outcomes using the Problem Based Learning (PBL) model in learning Pancasila and Civics Education in class IV UPT SDN 50 Kuranji Padang City in the nuances of the Merdeka Curriculum. This type of research is classroom action research using qualitative and quantitative approaches. The subjects of this research were 27 students of class IV UPT SDN 50 Kuranji Padang City in the January-June semester of the 2022/2023 school year. The results showed: First, in the first cycle teaching module making obtained an average percentage of 85.4% (B), increased in cycle II to 95.8% (SB). Second, the results of the implementation of learning aspects of the teacher in cycle I obtained an average of 82.14% (B), increasing in cycle II to 96.42% (SB). Third, the results of the implementation of learning aspects of students in cycle I obtained an average of 82.14% (B), increasing in cycle II to 96.42% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 76.82 (C), increasing in cycle II to 89.33 (B). It can be concluded that the Problem Based Learning model can improve student learning outcomes in learning Pancasila and Citizenship Education in class IV UPT SDN 50 Kuranji Padang City.